ON IMPROVED YOUNG TYPE INEQUALITIES FOR MATRICES - Hu, Xingkai; Yang, Fengzao; Xue, Jianming (Italian Journal of Pure and Applied Mathematics, 2015)
This paper aims to give improved Young type inequalities which are due to Hu [2]. Then we use these inequalities to establish corresponding Young type inequalities for matrices.